Animal-Related Fatalities in the United States (2018-2023) - Ricky L. Langley; Gregory D. Kearney (Environmental Health Insights)
Animal encounters are often positive but can result in serious injury, illness, or death, posing a global public health concern. Over 60% of human infectious diseases are zoonotic, contributing to millions of illnesses and deaths annually. Non-infectious injuries, including bites and stings, are also common, with snakebites alone causing over 100 000 deaths each year. The primary goal of this study was to describe fatal, animal-related encounters and assess trends from 2018 to 2023 in the United States. This was a secondary data analysis, using aggregate, population-level data obtained from the Centers for Disease Control and Prevention, Wide-ranging Online Data for Epidemiologic Research (CDC WONDER). Data was analyzed on 1604 total animal-related deaths, averaging 267 annually (crude death rate: 0.808 per 1 million population). Fatalities were stratified by cause, animal type (venomous vs nonvenomous), age, sex, race, ethnicity, and region. Overall, the major causes of death were from hornets, wasps, and bees (31.0%), “other mammals” (28.6%) and dogs (26.2%). Most decedents were male (67.6%), white (87.2%) and between 55 and 64 years old (22.8%). The Southern U.S. had the highest number (46.8%) and rate (0.984 per 1 million) of deaths. We observed an upward trend in animal-related fatalities, including a notable increase in human deaths caused by dogs during and following the COVID-19 pandemic. This rise is likely associated with the surge in pet adoptions and increased time spent at home during this period. Public health strategies that promote safe animal interactions, increased awareness, and responsible pet ownership may help mitigate these fatalities. Future research should aim to capture contextual factors, such as household dynamics, animal behavior, and environmental conditions to better inform targeted prevention efforts.